Implikasi Penggunaan El dan YHWH dalam Kekristenan Masa Kini - Eben Munthe (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2019)
The use of the terms El and YHWH relating to the name of God or God in the Bible produces a lot of discussion, in which groups eventually tend to maintain YHWH or Yahweh as names that cannot be replaced. The group is usually called Yahweism, or the admirers of the name Yahweh. This article provides a literature review with a qualitative approach to the texts of the Scriptures concerning the use of the term name. With descriptive and analytical methods, the conclusion is that the use of El and YHWH in the Old Testament refers to the same person so that it is not necessary to debate its use. El refers to revelation in general, while YHWH shows special revelation in the context of the election and salvation of a nation or people. AbstrakPenggunaan istilah El dan YHWH berkaitan dengan nama Allah atau Tuhan dalam Alkitab menghasilkan banyak diskusi, di mana pada akhirnya muncul kelompok yang cenderung mempertahankan YHWH atau Yahweh sebagai nama diri yang tidak boleh diganti. Kelompok tersebut biasa disebut Yahweisme, atau para pengagum nama Yahweh. Artikel ini memberikan kajian literature dengan pendekatan kualitatif pada teks-teks Kitab Suci berkenaan dengan penggunaan istilah nama tersebut. Dengan metode deskriptif dan analisis, maka diperoleh kesimpulan bahwa penggunaan El dan YHWH dalam Perjanjian Lama merujuk pada satu pribadi yang sama sehingga tidak perlu diperdebatkan penggunaannya. El menunjuk pada pewahyuan secara umum, sementara YHWH menunjukkan pewahyuan khusus dalam konteks pemilihan dan keselamatan sebuah bangsa atau umat.